Pernikahan Dini Di Kecamatan Juntinyuat Kabupaten Indramayu Tahun 2015 – 2016 - Zaenal Amri (UIN Sunan Kalijaga Yogyakarta, 2018)
Law number 1 of 1974 has governed marriage rules in Indonesia. The marriedage limit for 19-year-old and 16-year-old girls. But the reality in the field thereare still people who do underage marriage. Indramayu district had become one ofthe District with the largest number of early marriages in West Java Province,the PTA West Java recorded in 2015 in Indramayu district reached 450, in2016 as many as 347. Juntinyuat District is one area in Indramayu thatextends on the coast North and East Indramayu District. The formulation ofthe problem in this study about, what are the factors causing Early Marriage inDistrict Juntinyuat, what the efforts of the KUA and related Instantsi partiesin order to minimize and even prevent Early Marriage in Juntinyuat District,and how the sociology of Islamic law against the factors and efforts to preventmarriage early in Juntinyuat District, Indramayu District. Law seen from theperspective of sociology, law and enforcer can not be released with the object orsociety correlation that will not be separated, other than because society is the object, sociology perspective considers that effective law is the law that lives in society.